Arcabouços 3D (Scaffolds) à base de poli (hidroxibutirato), quitosana e fibroína da seda para engenharia tecidual - Macedo, Maria Erisfagna Ribeiro de (2017)
Materials based on polyhydroxybutyrate (PHB), chitosan (CHI) and fibroin (SF) are biocompatible and attractive for applications in bone tissue engineering. In this work, 3D scaffolds of PHB/CHI and PHB/CHI/SF in different proportions was prepared, characterized and evaluated the in vitro behavior: group I: PHB/CHI (50:50 wt.%), group II: PHB/CHI/SF (50:45:5 wt.%) and group III: PHB/CHI/SF (50:35:15 wt.%). The scaffolds were produced by the lyophilization method of the components mixtures. The physical-chemical characterization of the scaffolds was performed by X-ray diffraction, infrared spectroscopy, scanning electron microscopy and thermogravimetric analysis. A highly porous nature was revealed by SEM analysis of the scaffolds. The FTIR analysis revealed that the constituents used in the preparation of the scaffolds interacted chemically with each other. Thermal analysis showed that fibroin increases the thermal stability of the scaffolds. The viability and cell proliferation were assessed by the MTT method and the cytotoxicity results showed that all scaffolds are non- cytotoxic. In addition, the scaffolds stimulated cell proliferation and are promising for tissue engineering applications.